2021
DOI: 10.3390/agronomy11010160
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Ethylene in Physiological Processes Determining the Vase Life of Various Hybrids of Mokara Orchid Cut Flowers

Abstract: There is limited information about the postharvest performance and physiology of Mokara orchid cut flowers, which are a special group of artificially created trigenetic hybrids of Vanda × Arachnis × Ascocentrum. Therefore, we first characterized the patterns of various physiological parameters during vase life of five Mokara hybrids, which differ in their longevity. Then, we examined the effects of ethephon and ethylene inhibitors on these physiological parameters, and on parameters of the ethylene biosynthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Suitable handling, eco-friendly for a safe environment, non-harmful, and low price are mecessary because poor postharvest practices affect quality losses in cut flowers [19][20][21][22]. The most common symptoms are wilting senescence, which is linked to the loss of cell turgor pressure by a failure of water uptake due to stem blockage by air; microbial growth; and physiological plugging [23][24][25]. Additionally, leaf chlorophyll and petal pigments, such as anthocyanin, carotenoids, and betalains, decline, causing color fading, missing, or breakdown [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Suitable handling, eco-friendly for a safe environment, non-harmful, and low price are mecessary because poor postharvest practices affect quality losses in cut flowers [19][20][21][22]. The most common symptoms are wilting senescence, which is linked to the loss of cell turgor pressure by a failure of water uptake due to stem blockage by air; microbial growth; and physiological plugging [23][24][25]. Additionally, leaf chlorophyll and petal pigments, such as anthocyanin, carotenoids, and betalains, decline, causing color fading, missing, or breakdown [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to STS, the ET-action inhibitor 1-MCP also reduced ET production in cut rose, carnation, and lotus flowers by the suppression of ACS1 , ACS2 , and ACO1 ( Imsabai et al, 2010 ; In et al, 2013 ; Ha et al, 2020 ). Recently, Wang et al (2020) and Wongjunta et al (2021) observed that STS inhibited ET production in lotus leaves and orchid flowers by suppressing the expression of ACS and the activities of ACS and ACO enzymes. Moreover, ethephon-enhanced ET production, ACS and ACO expression, and ACS and ACO activities have also been reported in previous studies ( Imsabai et al, 2010 ; Lee et al, 2021 ; Nascimento et al, 2021 ; Wongjunta et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Wang et al (2020) and Wongjunta et al (2021) observed that STS inhibited ET production in lotus leaves and orchid flowers by suppressing the expression of ACS and the activities of ACS and ACO enzymes. Moreover, ethephon-enhanced ET production, ACS and ACO expression, and ACS and ACO activities have also been reported in previous studies ( Imsabai et al, 2010 ; Lee et al, 2021 ; Nascimento et al, 2021 ; Wongjunta et al, 2021 ). Taken together, these findings showed that ethephon completely prevented stem bending in the three different cultivars of snapdragon cut flowers and that STS significantly stimulated stem bending.…”
Section: Discussionmentioning
confidence: 99%
“…Senescence processes after harvest were investigated in cut flowers of Lilum [1], Peony [2][3][4], Lisianthus [5], and Mokara orchids [6], as well as in cut foliage of Polygonatum multiflorum 'Variegatum' [7]. Several authors studied the effects of various PGRs such as salicylic acid, gibberellin (GA 3 ) [1], ethylene [6] or 5-Aminolevulinic Acid (ALA) [7] on different senescence parameters in cut flowers of Lilium, Mokara orchid and cut foliage of Polygonatum multiflorum. These PGR treatments reduced the senescence and consequently improved the quality and extended the longevity of these ornamental systems, except for ethylene.…”
mentioning
confidence: 99%
“…These PGR treatments reduced the senescence and consequently improved the quality and extended the longevity of these ornamental systems, except for ethylene. Since ethylene is well-known as a senescence accelerator, its activity and biosynthesis inhibitors were found to reduce the senescence processes studied in cut flowers of the Mokara orchids [6].…”
mentioning
confidence: 99%